Galactomyces fermentation filtrate prevents T helper 2‐mediated reduction of filaggrin in an aryl hydrocarbon receptor‐dependent manner. (1st October 2015) - Takei, K.; Mitoma, C.; Hashimoto‐Hachiya, A.; Takahara, M.; Tsuji, G.; Nakahara, T.; Furue, M.
Summary: Background: The aryl hydrocarbon receptor (AhR) recognizes diverse small molecules such as dioxins, tryptophan photoproducts and phytochemicals. It also plays crucial roles in epidermal homeostasis by upregulating epidermal barrier proteins. In preliminary screening, we found that Galactomyces fermentation filtrate (GFF), a cosmetic compound, was capable of activating AhR. Aim: To examine whether GFF upregulates the expression of the filaggrin and loricrin genes, FLG and LOR, in an AhR‐dependent manner. Methods: The activation (cytoplasmic to nuclear translocation) of AhR was confirmed by immunofluorescence study and by upregulation of an AhR‐specific marker, cytochrome P450‐1A1 (CYP1A1). Gene expression levels were compared by quantitative reverse transcription PCR with or without GFF, interleukin (IL)‐4 or IL‐13 in normal human keratinocytes. AhR or control knockdown was carried out by transfection with AhR or control small interfering RNA. The protein expression of FLG and LOR was examined by immunohistochemistry using a three‐dimensional epidermal equivalent treated with or without GFF or T helper (Th)2 cytokines. Results: GFF induced the nuclear translocation of AhR with significant and dose‐dependent upregulation of CYP1A1, FLG and LOR gene expression. The enhancing effects of GFF were abolished in AhR‐knockdown keratinocytes. Th2 cytokines decreased expression of genes for FLG and LOR, and this expression was completely restored in the presence of GFF. The downregulated expression of the FLG gene with its restoration by GFF was also evident in the epidermal equivalent. GFF also upregulated the gene expression of genes encoding occludin, claudin‐1 and 4, and kallikrein 5 and 7. Conclusions: Use of GFF is feasible to prevent the Th2‐mediated reduction of FLG in an AhR‐dependent fashion.